Semiconductor Lasers Based on Quantum Well Structures - Pudis, Dusan; Kovac, Jr., J.; Kovac, J.; Jakabovic, J. (Communications - Scientific letters of the University of Zilina, 2003)
We present electrical and optical properties of the quantum well laser structures based on InAs / AlxGa1-x As material systems. The experimental results obtained from room- and low temperature electroluminescence measurements of InAs/Al0.40Ga0.60 As revealed the excellent emission spectra in the visible range 620-660 nm. The experimentally obtained transitions energies were compared with simple Kronig-Penney simulations. Going to low temperatures the stimulated emission from the cleaved edge was observed, which could be real perspective for laser applications.